Autoantibodies in the Pathogenesis, Diagnosis, and Prognosis of Juvenile Idiopathic Arthritis - Mahmud, Shawn A.; Binstadt, Bryce A. (Frontiers in Immunology, 2019)
Autoantibody production occurs in juvenile idiopathic arthritis (JIA) and numerous other autoimmune diseases. In some conditions, the autoantibodies are clearly pathogenic, whereas in others the roles are less defined. Here we review various autoantibodies associated with JIA, with a particular focus on antinuclear antibodies and antibodies recognizing citrullinated self-antigens. We explore potential mechanisms that lead to the development of autoantibodies and the use of autoantibody testing in diagnosis and prognosis. Finally, we compare and contrast JIA-associated autoantibodies with those found in adults with rheumatoid arthritis (RA).